Effect of attire on client perceptions of veterinarians. (November 2020) - Bentley, E.; Kellihan, H.; Longhurst, C.; Chun, R.
Highlights: Wearing a lab coat increased veterinary clients' perceived competency and comfort. Surgical scrubs increased perceived competency compared to business casual. Surgical scrubs increased comfort of clients compared to business casual. Abstract: This study examined the effect that veterinarian attire and gender had on clients' perceptions of veterinarians in a large academic specialty hospital. Clients volunteered to answer a survey in the small animal waiting area over a 3-month period. The survey consisted of demographic information, information about the nature of their appointment with their pet, and questions regarding clients' levels of comfort with and the perceived trustworthiness of a Caucasian male and Caucasian female model in four different types of attire: surgical scrubs, surgical scrubs with white lab coat, business casual, and business casual with white lab coat. Relevant effects of interest were estimated using linear mixed models. Five hundred and five clients participated in the survey, yielding a total of 6217 completed survey questions. Clients perceived veterinarians wearing white lab coats as more competent and reported more comfort with those veterinarians ( P < 0.0001). When comparing surgical scrubs with no white lab coat to business attire with no white lab coat, surgical scrubs resulted in higher perceived competence and comfort levels ( P < 0.0001). Wearing a white lab coat over both surgical scrubs and business casual increased clients' perceived competency and comfort levels compared to not wearing a white lab coat.